Multiple strictures of the small intestine demanding surgical intervention as a rare consequence of graft versus host disease - case report - Agnieszka Sobkowiak-Sobierajska; Michał Błaszczyński; Przemysław Mańkowski; Jacek Wachowiak (SpringerOpen, 2020)
Abstract Background Intestinal strictures are an extremely rare and life-threating complication in patients undergoing allogenic hematopoietic stem cell transplantation (allo-HSCT). We describe the case of a child operated for multiple strictures of the small intestine secondary to GvHD. Case presentation A 7-year-old girl underwent second allo-HSCT from matched unrelated donor for post-CALR-positive-ET myelofibrosis and its relapse after the first HSCT. HSCT was complicated with grade IV acute GvHD (skin and gut). The patient was treated with CsA, with methylprednisolone, and due to corticosteroid resistance subsequently with etanercept and ECP. She required parenteral nutrition due to malabsorption symptoms and anorexia for 15 months after HSCT. On day + 457, the laparotomy was performed due to increasing symptoms of mechanical bowel obstruction. Ten critical cicatricial strictures of the small intestine were revealed. Nine segmental resections of the strictured segments and 6 intestinal anastomoses were done during one surgical procedure. The postoperative period was uncomplicated, and oral feeding was gradually implemented, achieving full coverage. Pathological examination confirmed the diagnosis of overlap syndrome of acute and chronic GvHD. Therefore, the patient started therapy with ruxolitinib which was continued till 30 months after HSCT. Corticosteroids were gradually withdrawn on day + 574. Currently, 32 months after the second HSCT, no GvHD and no gastrointestinal disturbances are observed. The patient remains in hematological and molecular remission of myelofibrosis. Conclusions GvHD therapy is largely based on conservative treatment, but a patient presenting with occlusive symptoms due to permanent changes in the gastrointestinal wall needs to undergo surgery to ensure its efficient functioning.